A hot working method for improving the mechanical properties of titanium alloy fastener bar blanks

By combining upsetting deformation, uniform temperature extrusion, differential temperature extrusion and heat treatment processes, the problems of long flow, low material utilization and uneven tissue distribution in the preparation process of titanium alloy fastener rod blank are solved, and efficient preparation and excellent mechanical properties of rods are achieved.

CN115255018BActive Publication Date: 2025-04-25TIANJIN UNIV OF TECH & EDUCATION (TEACHER DEV CENT OF CHINA VOCATIONAL TRAINING & GUIDANCE) +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210615663.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-31
Publication Date
2025-04-25
Estimated Expiration
2042-05-31

AI Technical Summary

Technical Problem

The existing titanium alloy fastener blank preparation process has problems such as long preparation process, low material utilization rate, and uneven microstructure distribution, which cannot meet the high-quality needs in the aerospace field.

Method used

The combination of upsetting deformation, uniform temperature extrusion, differential temperature extrusion and heat treatment processes is adopted. Through multiple upsetting deformation and multiple extrusion treatments, the temperature difference inside and outside the blank is controlled to improve the microstructure uniformity and shear strength of the rod blank.

Benefits of technology

It significantly shortens the preparation cycle, improves the material utilization rate, and obtains excellent results in the microstructure uniformity of the rod and comprehensive mechanical properties, meeting the high-quality needs in the aerospace field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115255018B_ABST
    Figure CN115255018B_ABST
Patent Text Reader

Abstract

The present invention provides a hot processing method for improving the mechanical properties of titanium alloy fastener bar blanks, and processes titanium alloy materials through a process method combining smelting, upsetting, isothermal extrusion, differential temperature extrusion, isothermal extrusion, and heat treatment. The processing method can improve the uniformity of microstructure distribution from the core to the surface of the bar and the mechanical properties, and meet the mechanical requirements of titanium alloy fasteners. In addition, the method of the present invention has a small number of fires and a high material utilization rate, and has a wide range of practical value for the processing of titanium alloy fastener bar blanks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of titanium alloy material processing and forming, and in particular relates to a processing method for improving the thermodynamic properties of a titanium alloy fastener bar blank. Background Art

[0002] Titanium alloy is an alloy composed of titanium as the base and other alloying elements. Titanium alloy has the advantages of low density, high specific strength, good corrosion resistance, high heat resistance, and good process performance. At present, titanium alloy is the most widely used titanium metal material, and is widely used in aviation materials, oil extraction, food and sports, and medical fields.

[0003] Titanium alloy fasteners are widely used in the future aerospace field due to their high shear strength, corrosion resistance and fatigue resistance, and the demand for titanium alloy bars is huge. The conventional methods for preparing titanium alloy fastener bar blanks in my country are forging and rolling processes. The advantages of these two methods are mature processes and simple operations, while the disadvantages are long preparation processes, low material utilization, and uneven distribution of microstructure and mechanical properties from the core to the surface of the bar, with obvious anisotropy, which cannot meet the requirements of aerospace. Therefore, my country's titanium alloy fastener bar blanks are currently mainly imported. This situation has become a major bottleneck restricting the high-quality development of my country's domestic fasteners. How to solve this technical problem has posed a severe challenge to domestic research institutions and manufacturing companies.

[0004] At present, relevant units have proposed new processes to prepare homogeneous and high-strength titanium alloy fastener bar blanks. For example, a forming method that combines free forging and pulse current assisted extrusion to improve the uniformity of the titanium alloy bar structure (CN113493886B, Comparative Patent 1), and a process for preparing titanium alloy bar blanks by combining extrusion blanking with pulse current heat treatment (CN113416906B, Comparative Patent 2). However, these two new processes are not yet mature, have high requirements for equipment, and are limited to the range of bar processing size specifications, and are still far from industrialization and practicality. The technical solution of this application aims to combine differential temperature extrusion technology on top of the traditional process, on the one hand, to shorten the process and improve production efficiency; on the other hand, it can improve the microstructure uniformity and shear strength of the bar blank by controlling the temperature difference between the inside and outside of the blank. Summary of the invention

[0005] The purpose of the present invention is to provide a hot working method for improving the uniformity of the microstructure of titanium alloy fastener bar blanks and thus improving the mechanical properties in view of the deficiencies of the prior art. The method combines upsetting deformation, isothermal extrusion, differential temperature extrusion and heat treatment processes to prepare titanium alloy fastener bar blanks to improve the uniformity of the microstructure distribution from the core to the surface of the bar and the mechanical properties. Compared with traditional forging or rolling processes, the method proposed by the present invention has the advantages of fewer fires, high material utilization, uniform bar microstructure and excellent comprehensive mechanical properties.

[0006] To achieve the above objectives, this paper provides a hot working method for improving the mechanical properties of titanium alloy fastener rod blanks, which includes S1 smelting, S2 first upsetting, S3 second upsetting, S4 first isostatic extrusion, S5 differential temperature extrusion, S6 second isostatic extrusion, S7 solution heat treatment, and S8 aging heat treatment.

[0007] The technical solution adopted by the present invention specifically includes the following steps:

[0008] S1. Melting, obtaining a titanium alloy ingot by melting in a vacuum consumable arc furnace;

[0009] S2. The first upsetting process is to heat the ingot to T1 with the furnace, keep it at temperature for H1, and then perform two upsetting deformations. After the upsetting deformations are completed, the ingot is air-cooled to T2 and then returned to the furnace.

[0010] Preferably, in S2, the two upsetting and drawing deformations are specifically as follows: in the first upsetting and drawing deformation, the upsetting reduction amount is 60% of the original ingot height, the upsetting reduction rate is controlled within 20 mm / s, to prevent the surface cracking of the ingot, and the ingot is turned 90° after upsetting to be drawn to the original ingot height to ensure full anvil feeding; in the second upsetting and drawing deformation, the upsetting reduction amount for each time is 50% of the ingot height, the upsetting reduction rate is controlled within 10 mm / s, to prevent the surface cracking of the ingot, and the ingot is turned 90° after upsetting to be drawn to the original ingot height to ensure full anvil feeding; before each upsetting, the upper and lower molds are flame heated to 300-350°C, and the time for the ingot to be taken out of the furnace and transferred to the press is less than 50 seconds.

[0011] S3. The second upsetting, the material obtained in step S2 is heated to T3 with the furnace and kept at H2 hours for stress relief and homogenization annealing. After the end of the insulation, it is continued to be heated to T4 with the furnace, kept at H3, and two upsetting deformations are performed after the end of the insulation. After the upsetting, the bar is water-cooled to room temperature;

[0012] Further preferably, in step S3, the two-pass upsetting deformation is specifically as follows: the first upsetting deformation: the upsetting reduction is 60% of the original ingot height, the upsetting reduction rate is controlled within 20 mm / s, to prevent the surface cracking of the ingot, after the upsetting is completed, the ingot is turned 90° and drawn to 1.5 times the original ingot height, to ensure full anvil feeding; the second upsetting deformation: the upsetting reduction is 50% of the ingot height each time, the upsetting reduction rate is controlled within 10 mm / s, to prevent the surface cracking of the ingot, after the upsetting is completed, the ingot is turned 90° and drawn to 1.5 times the original ingot height, to ensure full anvil feeding; before each upsetting, the upper and lower molds are flame heated to 300-350°C, and the time for the ingot to be taken out of the furnace and transferred to the press is less than 50s;

[0013] S4. The first isothermal extrusion, the forged rod obtained in step S3 is heated to T5 and kept at H4 for stress relief and homogenization annealing, and then heated to T6 and kept at H5. After the end of the heat preservation, the first isothermal extrusion is performed. After the extrusion is completed, the rod is water-cooled to room temperature;

[0014] Further preferably, in step S4, the extrusion ratio is controlled between 2.5 and 3, the extrusion die temperature is preheated to 300-350°C, the transfer time from the ingot out of the furnace to the extrusion equipment is controlled within 50s, the extrusion speed is controlled at 40-50mm / s, and in order to reduce friction, the outer surface of the ingot and the inner wall of the extrusion barrel are evenly coated with glass lubricant.

[0015] S5. Differential temperature extrusion, heating the forged bar obtained in step S4 to T7 and holding it for H6, then performing stress relief and homogenization annealing, and combining finite element simulation analysis, continuing to heat it to T8 and holding it for H7, which can ensure that the core temperature of the bar is 20-30°C lower than the surface temperature; extrusion, after the extrusion is completed, water-cooling the bar to room temperature;

[0016] Further preferred is S5 differential temperature extrusion to further break and refine the as-cast structure and eliminate as-cast defects. After the extrusion is completed, water cooling is immediately performed to obtain a fine basket structure. The extrusion ratio is controlled between 2.0 and 2.5, the extrusion die temperature is preheated to 300-350°C, the ingot out of the furnace to the extrusion equipment transfer time is controlled within 50s, the extrusion speed is controlled at 40-50mm / s, and the outer surface of the ingot and the inner wall of the extrusion barrel are evenly coated with glass lubricant to reduce friction.

[0017] S6. The second isostatic extrusion is performed, wherein the material obtained in step S5 is heated to T9 and kept at temperature for H8 hours for stress relief and homogenization annealing, and then heated to T10 and kept at temperature for H9; the extrusion ratio is controlled between 4 and 5. After the extrusion is completed, the bar is water-cooled to room temperature to obtain the supercooled β phase and the transformed martensite α phase;

[0018] S7. Solution heat treatment, heating the material obtained in step S6 to T11, keeping it at H10 and then cooling it with water;

[0019] S8. Aging heat treatment: the material obtained in step S7 is heated to T12 in the furnace, kept at H11 and then air-cooled to obtain equiaxed primary α phase and fine dispersed secondary α phase, thereby improving the comprehensive mechanical properties of the material.

[0020] Among them, T1∈[1050℃, 1150℃], T2∈[300℃, 350℃], T3∈[550℃, 600℃], T4∈[1050℃, 1150℃], T5∈[550℃, 600℃], T6∈[T β +50℃, T β +100℃], T7∈[550℃, 600℃], T8∈[T β -60℃, T β -30℃], T9∈[550℃, 600℃], T10∈[T β -60℃, T β -30℃], T11∈[T β -60℃, T β -30℃], T12∈[550℃, 600℃]; where T β is the phase transition temperature of titanium alloy;

[0021] Among them, the holding time, H1 = (0.6 ~ 0.8) D minutes, H2∈[4h, 6h], H3 = (0.6 ~ 0.8) D minutes, H4∈[4h, 6h], H5 = (0.6 ~ 0.8) D minutes, H6∈[4h, 6h], H7 = (0.6 ~ 0.8) D minutes, H8∈[4h, 6h], H9 = (0.6 ~ 0.8) D minutes, H8∈[4h, 6h], H9 = (0.6 ~ 0.8) D minutes, H10 = (0.6 ~ 0.8) D minutes, H11∈[6h, 10h], where D is the diameter of the titanium alloy rod in millimeters.

[0022] The present invention proposes a method combining upsetting deformation, isothermal extrusion, differential temperature extrusion and heat treatment process, wherein the upsetting deformation is a double deformation in the β single phase region, which mainly breaks the casting structure and eliminates casting defects; the extrusion process includes isothermal extrusion and differential temperature extrusion; the isothermal extrusion process can effectively break the casting structure and eliminate casting defects, while the differential temperature extrusion can improve the microstructure uniformity of the bar through the reasonable coordination of the extrusion ratio and the temperature difference between the core and the edge. The heat treatment process includes stress relief annealing after extrusion and forging and solid solution and aging heat treatment after extrusion, which mainly improves the comprehensive mechanical properties of the bar.

[0023] The present invention proposes a method combining the uniform temperature + differential temperature extrusion process with the free forging upsetting process to prepare the bar blanks required for titanium alloy fasteners, which is expected to improve the uniform distribution of the microstructure and mechanical properties of the bar material, and provide high-quality bar blanks for the manufacture of aerospace titanium alloy fasteners.

[0024] The advantages and beneficial effects of the present invention are:

[0025] 1. Compared with the preparation of bars by simple free forging, the present invention has a short preparation cycle, a streamlined process, reduces the transportation time between each firing, and improves the material utilization rate. Figure 2 , Conventional titanium alloy bar preparation process: titanium alloy ingot → T β Temperature above multiple (3 to 5 times) upsetting (or rolling) deformation → T β Temperature below (3 to 5 fires) upsetting (or rolling) deformation → heat treatment after forging (or rolling) (2 fires) → mechanical rough processing → 1 fire solid solution + 1 fire aging heat treatment, and the preparation process proposed by the present invention is: titanium alloy ingot → first upsetting deformation (1 fire) → second upsetting deformation (1 fire) → above T β The first isostatic extrusion (single phase zone) (1st fire) → below T β The first differential temperature extrusion (two-phase zone) (1st fire) at temperature → below T β Temperature second isostatic extrusion (two-phase region) (1 fire) → first solution treatment (1 heat treatment) → first aging treatment (1 heat treatment). For example, Figure 2 By comparison, it can be seen that the number of fires is reduced from 10 to 14 in the conventional process to 7 in the present invention.

[0026] 2. The free forging proposed in the present invention is combined with the uniform temperature + differential temperature extrusion process to improve the forming accuracy of the bar. At the same time, due to the use of the extrusion process, the mechanical rough processing (such as cutting and other processes) of the traditional preparation process is omitted, and the material utilization rate can be increased from the conventional 55% to 70% of the present invention. The bar is subjected to three-way pressure during the extrusion process, which can increase the deformation of the bar and significantly refine the grains;

[0027] 3. The combination of free forging and uniform temperature + differential temperature extrusion process proposed in the present invention can significantly improve the uniform distribution of the microstructure of the cross section of the bar, improve the comprehensive mechanical properties of the material, reduce the anisotropy of the mechanical properties of the bar, and expand the preparation range of the bar size (conventional rolling is suitable for preparing bars with a diameter of less than 75 mm);

[0028] 4. Compared with the process of the patent "A forming method for improving the uniformity of titanium alloy bar structure by combining free forging and pulse current assisted extrusion" (Comparative Patent 1, CN113493886B), the present invention has the following advantages:

[0029] (1) The present invention proposes a method of multiple upsetting and drawing combined with uniform temperature + differential temperature extrusion, which can significantly refine the grain size in the surface area of ​​the rod. Therefore, compared with the published patent 1, the shear strength of the titanium alloy rod prepared by the method of the present invention is significantly higher than the shear strength value of the invention patent 1 (see Table 3), which can significantly improve the performance of the titanium alloy rod;

[0030] (2) The cost of preparing the rod is low, and there is no need to purchase an additional high-power pulse current power supply, which reduces the manufacturing cost of the rod; the equipment required for the method proposed by the present invention is all existing equipment, while the equipment involved in the aforementioned invention requires further modification by the user, which increases the complexity of equipment operation and the difficulty of subsequent maintenance;

[0031] (3) The size range of the rods prepared by the present invention is larger (≦300mm), while the size range of the rods prepared by the aforementioned invention patent is (20-50mm) due to the influence of the pulse power supply. Therefore, the application range of the present invention is wider and the promotion value is greater.

[0032] 5. Compared with the process of the patent "A process for preparing titanium alloy bar billets by combining extrusion blanking with pulse current heat treatment" (Comparative Patent 2, CN113416906B), the method proposed by the present invention has the following advantages:

[0033] (1) The shear strength value of the titanium alloy rod prepared by the method of the present invention is higher than the shear strength value of the rod prepared by the method described in Invention Patent 2. The main reason is that in Invention Patent 2, the subsequent heat treatment is carried out by electric current, and the resistance of the microscopic defect area inside the material is relatively high, so the Joule heat in these areas causes a significant temperature rise, which causes these areas to melt in advance and then develop into micro crack sources, thereby accelerating the occurrence of material fracture, so the shear fracture resistance value is relatively low;

[0034] (2) The present invention adopts free forging to produce blanks, so the specification range of the prepared bars is larger (≦300mm), while the extrusion process is limited by the tonnage of the press, and the specification range of the prepared bars is smaller, which is only suitable for the preparation of blanks within the range of 20 to 50mm;

[0035] (3) The present invention does not require the purchase of a high-power pulse current power supply, which increases the manufacturing cost. The present invention has market promotion value. Comparative Document 2 uses pulse current for subsequent heat treatment, which requires high precision control of the current value. Otherwise, the heat treatment temperature is likely to be too high or too low. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.

[0037] Figure 1: Process flow chart of titanium alloy bar preparation of the present invention;

[0038] Figure 2 : Comparison diagram of the preparation process of the present invention and the traditional forging / rolling process;

[0039] Figure 3 : Schematic diagram of the sampling position of the metallographic structure of titanium alloy rod;

[0040] Figure 4 :Comparison diagram of metallographic structure of different sampling positions of bar material in implementation case 1 with traditional forging and rolling preparation;

[0041] Figure 5 :Comparison diagram of metallographic structure of different sampling positions of bar material in implementation case 2 with traditional forging and rolling preparation;

[0042] Figure 6 : Schematic diagram of sampling location for shear strength test of titanium alloy bar. DETAILED DESCRIPTION

[0043] The following embodiments are combined with the examples to describe the specific embodiments of the present invention in more detail, so as to better illustrate the scheme of this aspect and its advantages in various aspects. It should be pointed out that the purpose of the specific embodiments and embodiments described below is only to illustrate, and is not to limit the present invention. The instruments, reagents, materials, etc. involved in the following embodiments, if not otherwise specified, are all conventional instruments, reagents, materials, etc. already in the prior art, and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following embodiments, if not otherwise specified, are all conventional experimental methods, detection methods, etc. already in the prior art. All other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0044] like Figure 1 As shown in the flow chart, the processing technology of the present invention follows the following process.

[0045] 1. Titanium alloy ingot melting

[0046] The titanium alloy ingots involved in the present invention are all obtained by three smeltings in a vacuum consumable arc furnace. After smelting, the ingot is cooled in a water-cooled copper crucible. The cooling process of the ingot requires strict control of the cooling water temperature and cooling time. The cooling water inlet temperature is controlled at 25-28°C, the cooling water outlet temperature is controlled between 28-31°C, and the cooling water flow rate is controlled by controlling the difference between the outlet temperature and the inlet temperature to be less than 3°C. When the ingot is cooled, it is necessary to quickly take the ingot out of the water-cooled copper crucible and wrap it with asbestos or put it in an electric furnace with a temperature of ≤400°C to cool it to room temperature.

[0047] 2. The first upsetting deformation

[0048] The titanium alloy ingot is heated from room temperature to T1 with the furnace, and kept at temperature for H1 time; the first upsetting deformation: the upsetting reduction is 60% of the original ingot height, and the upsetting reduction rate is controlled within 20mm / s to prevent the surface cracking of the ingot. After upsetting, the ingot is turned 90° and drawn to the original ingot height to ensure full anvil feeding; the second upsetting deformation: the upsetting reduction for each time is 50% of the ingot height, and the upsetting reduction rate is controlled within 10mm / s to prevent the surface cracking of the ingot. After upsetting, the ingot is turned 90° and drawn to the original ingot height to ensure full anvil feeding; before each upsetting, the upper and lower molds are flame heated to 300-350℃, and the time for the ingot to be taken out of the furnace and transferred to the press is controlled within 50s; after two upsettings, the bar is air-cooled to T2 and returned to the furnace.

[0049] 3. Second upsetting deformation

[0050] The forged rods are heated to T3 in the furnace and kept at the temperature for H2 hours, and then subjected to stress relief and homogenization annealing treatments. After the end of the heat preservation, they are further heated to T4 in the furnace and kept at the temperature for H3. After the end of the heat preservation, they are subjected to two upsetting and two drawing deformations. The first upsetting deformation: the upsetting reduction is 60% of the original ingot height, and the upsetting reduction rate is controlled within 20mm / s to prevent the surface cracking of the ingot. After upsetting, the ingot is turned 90° and drawn to 1.5 times the original ingot height to ensure full anvil feeding; the second upsetting deformation: the upsetting reduction for each time is 50% of the ingot height, and the upsetting reduction rate is controlled within 10mm / s to prevent the surface cracking of the ingot. After upsetting, the ingot is turned 90° and drawn to 1.5 times the original ingot height to ensure full anvil feeding; before each upsetting, the upper and lower molds are flame heated to 300-350℃, and the time for the ingot to be taken out of the furnace and transferred to the press is controlled within 50s; after two upsettings, the bar is water-cooled to room temperature.

[0051] 4. The first isostatic extrusion

[0052] The water-cooled forged rods are heated to T5 and kept at H4 for stress relief and homogenization annealing, and then heated to T6 and kept at H5. The extrusion ratio is controlled between 2.5 and 3, the extrusion die temperature is preheated to 300-350°C, the transfer time from the ingot out of the furnace to the extrusion equipment is controlled within 50s, and the extrusion speed is controlled at 40-50mm / s. In order to reduce friction, the outer surface of the ingot and the inner wall of the extrusion barrel are evenly coated with glass lubricant. After the extrusion is completed, the rods are water-cooled to room temperature.

[0053] 5. The first differential temperature extrusion

[0054] The forged rods after extrusion are heated to T7 and kept warm for 6 hours for stress relief and homogenization annealing. After verification by finite element simulation analysis, they are further heated to T8 and kept warm for 7 hours to ensure that the core temperature of the rod is 20-30°C lower than the surface layer; extrusion is performed to further break and refine the cast structure and eliminate cast defects. After extrusion, the rods are immediately water-cooled to obtain fine basket structure. The extrusion ratio is controlled between 2.0 and 2.5, the extrusion die temperature is preheated to 300-350°C, the transfer time from the ingot out of the furnace to the extrusion equipment is controlled within 50s, and the extrusion speed is controlled at 40-50mm / s. In order to reduce friction, the outer surface of the ingot and the inner wall of the extrusion barrel are evenly coated with glass lubricant. After extrusion, the rods are water-cooled to room temperature.

[0055] 6. Second temperature isostatic extrusion

[0056] The forged rod after extrusion is heated to T9 in the furnace and kept at this temperature for 8 hours for stress relief and homogenization annealing, and then heated to T10 in the furnace and kept at this temperature for 9 hours. The extrusion ratio is controlled between 1.5 and 2.0, the extrusion die temperature is preheated to 300-350°C, the transfer time from the ingot out of the furnace to the extrusion equipment is controlled within 50s, and the extrusion speed is controlled at 40-50mm / s. In order to reduce friction, the outer surface of the ingot and the inner wall of the extrusion barrel are evenly coated with glass lubricant. After the extrusion is completed, the rod is water-cooled to room temperature.

[0057] 7. First solution treatment

[0058] The extruded bar material is heated to T11 in a furnace and then kept warm for T10; it is then water-cooled to obtain a supercooled β phase and a transformed martensite α phase.

[0059] 8. First aging treatment

[0060] The above materials were heated in a furnace to the T12 range, kept warm for H11 hours and then air-cooled. Specific embodiment:

[0062] Example 1: Ti6554 rod preparation

[0063] The chemical composition of Ti6554 titanium alloy is (%, mass percentage): 5.7 chromium, 4.7 molybdenum, 4.8 vanadium, 3.9 aluminum, 0.08 iron, 0.028 silicon, 0.025 carbon, and the rest titanium. The phase transition temperature T of Ti6554 β=820℃, which belongs to a high-strength and tough near-β titanium alloy with a high content of alloying elements. After three vacuum consumable arc furnace smelting, removal of water risers and rough processing, a 50kg cylindrical ingot (diameter 300mm×height 150mm) was obtained. The specific smelting parameters are shown in Table 1. The above Ti6554 cylindrical ingot was subjected to upsetting deformation in steps S2 and S3 to obtain a cylindrical bar with a height of 225mm; after extrusion in step S4, a cylindrical bar with a diameter of 140mm was obtained; after step S5, a cylindrical bar with a diameter of 90mm was obtained; finally, after step S6, a cylindrical bar with a diameter of 40mm was obtained; after the solid solution and aging treatment described in S7 and S8, the Ti6554 titanium alloy bar blank prepared by the present invention was finally obtained. Among them, the temperature and time parameters involved in S2 to S8 are shown in Table 2.

[0064] Table 1 Titanium alloy ingot melting process parameters

[0065] Process parameters One smelting Secondary smelting Three smelting Vacuum before melting / Pa <![CDATA[≤1.33×10 -2 ]]> <![CDATA[≤1.33×10 -2 ]]> <![CDATA[≤1.33×10 -2 ]]> Arc starting current / KA 1 2.4 2.8 Arc stabilization current / A 1.5 1.5 1.5 Melting current / KA 1.0~1.2 2.0~2.7 3.0~3.5 Melting voltage / V 20~25 22~28 22~28 Melting vacuum / Pa <![CDATA[≤6.67×10 -1 ]]> <![CDATA[≤6.67×10 -1 ]]> <![CDATA[≤6.67×10 -1 ]]> Inlet water temperature / ℃ ≤25 ≤25 ≤25 Outlet water temperature / ℃ ≤30 ≤30 ≤30 Cooling time / min ≥20 ≥50 ≥90

[0066] Table 2 Preparation process parameters of Ti6554 titanium alloy bars

[0067]

[0068] The titanium alloy bars prepared according to the above process parameters are as follows: Figure 3 The sampling locations shown in the figure are respectively sampled at positions 1, 2, and 3 to make metallographic organization diagrams. Figure 3 Among the sampling positions, position 1 is the sampling at the center; position 2 is the sampling at 1 / 2 radius; position 3 is the sampling at the edge.

[0069] Attached Figure 4 The titanium alloy bars prepared for Example 1 were sampled at different sampling locations (see Appendix Figure 3 The metallographic organization diagram of the titanium rod prepared by the conventional forging and rolling methods is compared. Among them, in alphabetical order, (a) to (c) are metallographic diagrams of different positions of the rod prepared by the patented method of the present invention, (d) to (f) are metallographic diagrams of different positions of the rod prepared by free forging, and (g) to (i) are metallographic diagrams of different positions of the rod prepared by rolling; Appendix Figure 4 Among them, (a), (d), (g) are metallographic images of position 1, (b), (e), (h) are metallographic images of position 2, and (c), (f), (i) are metallographic images of position 3. It is obvious that the metallographic organization diagram of the present application shows that the internal structure is more uniform and compact.

[0070] According to the attached Figure 6The sampling positions are as follows: position 1: edge sampling, position 2: core sampling, and position 3: sampling at 1 / 2 radius. The Ti6554 rods prepared by the process of the present invention and the Ti6554 rods prepared by the process of the comparative patent 1CN113493886B were sampled at the corresponding positions to detect the shear strength values. The obtained data are shown in Table 3.

[0071] Table 3 Comparison of shear strength of Ti6554 titanium alloy bars prepared by the present invention and those prepared by patent 1CN113493886B

[0072]

[0073] Example 2: Ti55531 rod preparation

[0074] The chemical composition of Ti55531 titanium alloy is (%, mass percentage): aluminum 5.3, molybdenum 5.2, vanadium 5.2, chromium 2.65, zirconium 1.02, and the rest titanium. The phase transition temperature T of Ti55531 β =845℃, which belongs to a high-strength and tough near-beta titanium alloy with a high content of alloying elements, so a vacuum consumable arc furnace is used for three smeltings to obtain a 50kg ingot (diameter 300mm×150mm), and the smelting parameters are the same as those shown in Table 1. The above Ti6554 cylindrical ingot is subjected to upsetting deformation in steps S2 and S3 to obtain a cylindrical bar with a height of 225mm; a cylindrical bar with a diameter of 140mm is obtained by extrusion in step S4; a cylindrical bar with a diameter of 90mm is obtained by step S5; finally, a cylindrical bar with a diameter of 40mm is obtained by step S6; after the solution and aging treatment described in S7 and S8, the Ti55531 titanium alloy bar blank prepared by the present invention is finally obtained. Among them, the temperature and time parameters involved in S2 to S8 are shown in Table 4.

[0075] Table 4 Preparation process parameters of Ti55531 titanium alloy bars

[0076]

[0077] The titanium alloy rods are prepared according to the Figure 3 The sampling locations shown in the figure are respectively sampled at positions 1, 2, and 3 to make metallographic organization diagrams. Figure 5 The metallographic organization diagrams of titanium alloy bars prepared in Example 2 at different sampling positions are compared with those of titanium bars prepared by traditional forging and rolling methods. Among them, in alphabetical order, (a) to (c) are metallographic diagrams of bars prepared by the patented method of the present invention at different positions, (d) to (f) are metallographic diagrams of bars prepared by free forging at different positions, and (g) to (i) are metallographic diagrams of bars prepared by rolling at different positions; Appendix Figure 4Among them, (a), (d), (g) are metallographic images of position 1, (b), (e), (h) are metallographic images of position 2, and (c), (f), (i) are metallographic images of position 3. It is obvious that the metallographic organization diagram of the present application shows that the internal structure is more uniform and compact.

[0078] According to the attached Figure 6 The sampling positions are as follows: position 1: edge sampling, position 2: center sampling, and position 3: sampling at 1 / 2 radius. Figure 6 The Ti55531 titanium alloy rods prepared by the process of the present invention and the Ti55531 titanium alloy rods prepared by the process of the comparative patent 2CN113416906B were sampled at corresponding positions to detect the shear strength values. The obtained data are shown in Table 5.

[0079] Table 5 Comparison of shear strength of Ti55531 titanium alloy bars prepared by the present invention and prepared by Patent 2 (CN113416906B)

[0080]

[0081] The microstructure of the titanium alloy rods prepared in the above-mentioned Examples 1 and 2. Among them, the microstructure detection adopts conventional metallographic preparation and corrosion technology, the Ti6554 corrosion solution adopts: a mixture of hydrofluoric acid, nitric acid and water, and the volume ratio is 1:2:5; the Ti55531 corrosion solution adopts: a mixture of hydrochloric acid, nitric acid and water, and the volume ratio is 1:1:16. The microstructure is observed under an optical microscope, and the Image-pro software is used to count the grain size and volume fraction (i.e., area fraction) of the primary alpha grains. And compared with the microstructure obtained by conventional forging and rolling processes, such as Figure 4 , 5 It can be seen that the microstructure and mechanical properties of the titanium alloy rod prepared by the method proposed in the present invention are better than those of the conventional preparation method, which is mainly reflected in the further refinement and uniform distribution of the primary alpha grains.

[0082] The above is a further detailed description of the present invention in combination with specific preferred embodiments, and it cannot be considered that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the concept of the present invention.

Claims

1. A hot working method for improving the mechanical properties of titanium alloy fastener bar blanks, characterized in that: The hot working steps include S1 smelting, S2 first upsetting, S3 second upsetting, S4 first isothermal extrusion, S5 differential temperature extrusion, S6 second isothermal extrusion, S7 solution heat treatment, and S8 aging heat treatment; specifically, the following steps are included: S1, smelting, obtaining titanium alloy ingots by smelting in a vacuum consumable arc furnace; S2, the first upsetting deformation, the ingot is heated to T1 temperature with the furnace, kept at temperature for H1, and then subjected to two upsetting deformations, and then air-cooled to T2 temperature and returned to the furnace; S3. The second upsetting deformation, the material obtained in step S2 is heated to T3 temperature with the furnace and kept for H2 time, stress relief and homogenization annealing treatment, and the insulation is continued to be heated to T4 with the furnace after the end, the insulation time is H3, and two upsetting deformations are performed after the end of the insulation, and the bar is cooled to room temperature after the upsetting; S4. The first isothermal extrusion, the forged rod of step S3 is heated to T5 and kept for H4 hours for stress relief and homogenization annealing, and then heated to T6 and kept for H5 time. After the end of the isothermal extrusion, the first isothermal extrusion is performed, and after the extrusion is completed, the extrusion is cooled to room temperature; S5 differential temperature extrusion, heating the material obtained in step S4 to T7 and keeping it at H6 for stress relief and homogenization annealing, and continuing to heat it to T8 and keeping it at H7 to ensure that the core temperature of the bar is 20-30°C lower than the surface; extrusion is performed, and after the extrusion is completed, the bar is water-cooled to room temperature; S6, second isostatic extrusion, heating the material obtained in step S5 to T9 and keeping it at a temperature of H8, then performing stress relief and homogenization annealing, continuing to heat it to T10 and keeping it at a temperature of H9, and then performing extrusion. After the extrusion is completed, the bar material is water-cooled to room temperature; S7, solution heat treatment, the material obtained in step S6 is heated to T11 in the furnace, kept at temperature H10, and then water-cooled to obtain supercooled Mutually; S8, aging heat treatment, the material obtained in S7 is heated to T12 in the furnace, and then kept warm for H11 after being evenly heated, and then air-cooled; Wherein, T1∈[1050℃, 1150℃], T2∈[300℃, 350℃], T3∈[550℃, 600℃], T4∈[1050℃, 1150℃], T5∈[550℃, 600℃], T6∈[T β +50℃, T β +100℃], T7∈[550℃, 600℃], T8∈[T β -60℃, T β -30℃], T9∈[550℃, 600℃], T10∈[T β -60℃, T β -30℃], T11∈[T β -60℃, T β -30℃], T12∈[550℃, 600℃]; where T β is the phase transition temperature of titanium alloy; Wherein, the holding time, H1=(0.6~0.8)D minute, H2∈[4h, 6h], H3=(0.6~0.8)D minute, H4∈[4h, 6h], H5=(0.6~0.8)D minute, H6∈[4 h, 6 h], H7=(0.6~0.8)D minute, H8∈[4 h, 6h], H9=(0.6~0.8)D minute, H10=(0.6~0.8)D minute, H11∈[6 h, 10 h], wherein D is the diameter of the titanium alloy rod in millimeters.

2. A hot working method for improving the mechanical properties of titanium alloy fastener bar blanks according to claim 1, characterized in that: The two upsetting deformations in step S2, wherein, in the first upsetting deformation, the upsetting reduction is 60% of the original ingot height, the upsetting reduction rate is less than 20 mm / s, and after the upsetting is completed, the ingot is turned 90° and drawn to the original ingot height to ensure full anvil feeding; in the second upsetting deformation, the upsetting reduction is 50% of the ingot height, the upsetting reduction rate is less than 10 mm / s, and after the upsetting is completed, the ingot is turned 90° and drawn to the original ingot height to ensure full anvil feeding; before each upsetting, the upper and lower molds are flame heated to 300-350°C, and the time for the ingot to be taken out of the furnace and transferred to the press is less than 50s.

3. A hot working method for improving the mechanical properties of titanium alloy fastener bar blanks according to claim 1, characterized in that: The two-pass upsetting deformation described in step S3, wherein, in the first upsetting deformation, the upsetting reduction amount is 60% of the original ingot height, the upsetting reduction rate is less than 20 mm / s, and after the upsetting is completed, the ingot is turned 90° and drawn to 1.5 times the original ingot height to ensure full anvil feeding; in the second upsetting deformation, the upsetting reduction amount is 50% of the ingot height, the upsetting reduction rate is less than 10 mm / s, and after the upsetting is completed, the ingot is turned 90° and drawn to 1.5 times the original ingot height to ensure full anvil feeding; before each upsetting, the upper and lower molds are flame heated to 300~350℃, and the time for the ingot to be taken out of the furnace and transferred to the press is less than 50s.

4. A hot working method for improving the mechanical properties of titanium alloy fastener bar blanks according to claim 1, characterized in that: In step S4, the extrusion ratio is controlled between 2.5 and 3, the extrusion die temperature is preheated to 300-350° C., the transfer time from the ingot to the extrusion equipment is less than 50 seconds, the extrusion speed is controlled at 40-50 mm / s, and in order to reduce friction, the outer surface of the ingot and the inner wall of the extrusion barrel are evenly coated with glass lubricant.

5. The hot working method for improving the mechanical properties of titanium alloy fastener bar blanks according to claim 1, characterized in that: In step S5, the extrusion ratio is controlled between 2.0 and 2.5, the extrusion die temperature is preheated to 300-350° C., the ingot transfer time from the furnace to the extrusion equipment is less than 50 s, the extrusion speed is controlled at 40-50 mm / s, and the extrusion is immediately cooled by water after the extrusion is completed.

6. The hot working method for improving the mechanical properties of titanium alloy fastener bar blanks according to claim 5 is characterized in that: To reduce friction, glass lubricant is evenly applied to the outer surface of the ingot and the inner wall of the extrusion barrel.

Citation Information

Patent Citations

  • A process for preparing titanium alloy billets by combining extrusion blanking with pulsed current heat treatment.

    CN113416906B

  • A forming method for improving the microstructure uniformity of titanium alloy bars by combining free forging and pulsed current assisted extrusion.

    CN113493886B

  • Method for preparing and forming high-strength high-toughness wrought magnesium alloy

    CN105603283A

  • Forming method for improving structure uniformity of titanium alloy bar by combining free forging and pulse current auxiliary extrusion

    CN113493886A

  • Method for improving structure uniformity of near-beta titanium alloy fastener bar billet

    CN114182186A